2023
DOI: 10.1002/vms3.1071
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation therapy combined with static magnetic field in tibial fracture healing of a dog: A case report

Abstract: A 10-week-old male, Xoloitzcuintle (Mexican hairless dog), weighing 8.9 kg was presented after its owner accidentally stepped on its paw. The dog presented with acute pain, inflammation and grade IV lameness in the right hind paw. A complete transverse fracture in the right proximal tibia was diagnosed from radiography. The dog underwent a minimally invasive plate osteosynthesis (MIPO) procedure. After surgery, photobiomodulation therapy combined with static magnetic field (PBMT-sMF) was applied twice daily fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…During bone regeneration, histologically, we observe a tissue with fibroblasts, responsible for the deposition of collagen fibers; osteoblasts, which act in the formation of the bone matrix; osteoclasts that act in bone resorption and formation of vessels that carry nutrients and cells to the site of regeneration [81][82][83]. The immunohistochemical technique detected the presence of OCN (in the connective tissue and on the surface of the newly formed bone tissue over the biomaterial particles), and TRAP (present in the osteoblasts bordering the newly formed bone tissue and in some fibroblasts).…”
Section: Discussionmentioning
confidence: 99%
“…During bone regeneration, histologically, we observe a tissue with fibroblasts, responsible for the deposition of collagen fibers; osteoblasts, which act in the formation of the bone matrix; osteoclasts that act in bone resorption and formation of vessels that carry nutrients and cells to the site of regeneration [81][82][83]. The immunohistochemical technique detected the presence of OCN (in the connective tissue and on the surface of the newly formed bone tissue over the biomaterial particles), and TRAP (present in the osteoblasts bordering the newly formed bone tissue and in some fibroblasts).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research found that the external exposure to MMF could alleviate bone loss in mice [15,16]. Asteinza Castro IM et al found that 35 mT SMF can enhance the effect of photobiotherapy on promoting fracture healing in dog [17]. However, the effects of MMFs on fracture healing and the state of bone metabolism during this process is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research found that the external exposure to MMF could alleviate bone loss in mice [15,16]. Asteinza Castro IM et al found that 35 mT SMF can enhance the effect of photobiotherapy on promoting fracture healing in dog [17].…”
Section: Introductionmentioning
confidence: 99%
“…There are a few studies looking into photobiomodulation therapy and bone healing. In one case report, a 10-week-old male Xoloitzcuintle (Mexican hairless dog) that broke its tibia and was treated with surgical fixation as well as photobiomodulation therapy with a static magnetic field showed accelerated and improved bone healing following the surgical procedure [19]. Another study of rabbits evaluated photobiomodulation therapy as a treatment for osteochondral lesions of the knee, and after 24 weeks of photobiomodulation therapy, the treated knees had better cell morphology and repaired osteocartilaginous tissue compared to the non-treated knees [20].…”
Section: Introductionmentioning
confidence: 99%